The impact of sustainable development goals (SDGs) on tourism growth. Empirical evidence from G-7 countries - Mohammad Jibran Gul Wani; Nanthakumar Loganathan; Abdulwahab Mujalli (Cogent Social Sciences)
In light of the increasing worldwide apprehension regarding environmental sustainability, it has become imperative to understand the intricacies that exist between a sustainable environment, economic growth, and tourism growth. This study focuses on sustainable development goals (SDGs) and their relationship to tourism development. Therefore, the current study investigates the relationship between the primary dimensions of sustainability, such as economic, environmental, and social sustainability, and the growth of tourism in G7 countries, using data from 2000 to 2021. After establishing the cointegration between the variables using the Westerlund cointegration test, the long-run and short-run estimations of coefficients were carried out using the Panel ADRL framework (PMG). The results of the PMG test indicate that in the long run, economic growth and CO2 emissions have a positive and significant relationship with tourism growth, whereas ecological footprint, human development, and unemployment have a negative and significant relationship. However, in the short run, only economic growth and unemployment had significant coefficients and negative relationships with tourism development. Finally, this study investigated the causal direction of the variables using the Dumitrescu Hurlin causality test. A unidirectional causal link exists between tourism growth and GDP, ecological footprint, CO2, unemployment, and the human development index. The results also suggest that economic growth encourages tourism development, validating the growth-led tourism hypothesis. The policy implication of this study is that to achieve overall sustainability, the tourism industry has to develop environmentally friendly practices with a focus on economic and social well-being.